A New Validated HPLC-MS/MS Method for Quantification and Pharmacokinetic Evaluation of Dovitinib, a Multi-Kinase Inhibitor, in Mouse Plasma - AlRabiah H; Kadi AA; Aljohar HI; Attwa MW; Al-Shakliah NS; Attia SM; Mostafa GAE (Dove Medical Press, 2020)
Haitham AlRabiah,1 Adnan A Kadi,1 Haya I Aljohar,1 Mohamed W Attwa,1 Nasser S Al-Shakliah,1 Sabry M Attia,2 Gamal AE Mostafa1,3 1Department of Pharmaceutical Chemistry, College of Pharmacy, King Saud University, Riyadh 11459, Saudi Arabia; 2Department of Pharmacology Toxicology, College of Pharmacy, King Saud University, Riyadh 11451, Saudi Arabia; 3Micro-Analytical Laboratory, Applied Organic Chemistry Department, National Research Center, Dokki, Cairo, EgyptCorrespondence: Gamal AE Mostafa, Email gmostafa@ksu.edu.saBackground: Dovitinib (TKI 258) is a small-molecule multi-kinase inhibitor for the treatment of different types of cancer. There is currently no validated method for its quantitative determination; therefore, we aimed to develop a reliable method to assay dovitinib.Method and Results: An electrospray ionization tandem mass spectrometry (ESI-MS/MS) method was used to separate dovitinib using an analytical C18 column (50 × 2.1 mm, 1.8 μm) at 25°C. Bosutinib was used as the internal standard (IS). Dovitinib was extracted from mouse plasma using a precipitation procedure. The mobile phase consisted of 10 mM ammonium formate: acetonitrile (68:32, v/v, pH 4.3) run at a rate of 0.3 mL min− 1. MS detection was performed in the positive ion mode. Multiple reaction monitoring transitions were 393→ 337 and 393→ 309 for dovitinib, and 530→ 141 and 530→ 113 for bosutinib. The investigated method was validated as a bio-analytical method based on FDA guidelines. The linearity of the developed method was over the range of 5– 500 ng mL,− 1 coefficient of determination (r2= 0.9998). The average intra-day recovery and relative standard deviation (RSD) of the quality control (QC) sample were 97.24% and 1.32%, whereas the overall inter-day accuracy and precision were 97.99% and 0.54%, respectively. Dovitinib was stable during sample storage and handling conditions. Furthermore, the dilution integrity of the method was demonstrated by good recovery (97– 99%) and RSD values (0.5– 0.7%).Conclusion: This method was selectively sensitive and exhibited no matrix effect, with an acceptable accuracy and precision according to the FDA guidelines. The developed method could be efficiently used for pharmacokinetic studies of dovitinib.Keywords: HPLC, MS detection, dovitinib, mouse plasma, pharmacokinetics